Żydzi nad środkową Odrą. Transfer i wzajemne powiązania na polsko-niemieckim pograniczu od średniowiecza do XX wieku. Stan badań, źródła i projekty historii stosowanej = Jews on the Middle Oder. Transfer and interconnection in the German-Polish borderland from the Middle Ages to the 20th century. Research status, sources and applied history projects - Abraham-Diefenbach, Magdalena; Stürmer, Rhena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the treated area, Jews made up to about 2% of the population at different times. They were therefore a small minority. Traces of their presence can still be found in the form of Jewish cemeteries or synagogue buildings in the region.
Keywords: Żydzi; pogranicze polsko-niemieckie; Brandenburgia; Lubuskie; Jews; German-Polish border region; Brandenburg